The influence of leadership style, social support and workload toward stress among nurses - Nor Idayu, Zakaria (2016)
The purpose of the study is to investigate the relationship between leadership style, social support and workload with stress among nurses in Gua Musang Hospital, Kelantan. The health professionals are a group at significant risk from the negative effects of stressful including nurses. Through this study, data were collected successfully from 96 nurses of Gua Musang Hospital and data were analyzed using Statistical Package for Social Science (SPSS) version 22.0. Techniques of data analysis used in this study are frequency analysis, descriptive analysis and reliability analysis. Pearson correlation analysis was performed to examine the relationship between leadership style, social support and workload with stress and also to answer the objective of this research. Besides that, multiple regression analysis is conducted to analyse the relationship between independent variables and dependent variable. From the research finding, it provides better understanding of the factor influence the stress among nurses. The findings revealed that social support and workload was significantly influence to the stress while leadership style was not significantly influence to the stress.